2011
DOI: 10.1109/tsp.2011.2159499
|View full text |Cite
|
Sign up to set email alerts
|

Multipacket Reception of Passive UHF RFID Tags: A Communication Theoretic Approach

Abstract: This work develops a communication theoretic model for the design and analysis at the physical layer of a reader receiver structure for passive UHF RFID. The objective is attaining multi-packet reception capabilities which in turn help the fast resolution of multiple tags through a more rapid and power efficient arbitration of the tags collisions. In particular, we derive a parametric continuous time model for the subspace of a tag signal at the noisy receiver/reader, which in addition to being affected by fad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 18 publications
0
51
0
1
Order By: Relevance
“…Moreover, in [12], we have identified a potential throughput increase of more than five times in the case of a reader that can recover from a collision of up to eight tags in one slot and acknowledge two of them. Fyhn et al showed that channel fading, the difference in delay and the tag frequency dispersion can be used for easier separation of colliding signals in a multipacket receiver in [13]. In [14], Ricciato et al achieved a 20% to 25% gain in throughput by applying inter-frame successive interference cancellation (ISIC) with respect to traditional intra-frame SIC.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, in [12], we have identified a potential throughput increase of more than five times in the case of a reader that can recover from a collision of up to eight tags in one slot and acknowledge two of them. Fyhn et al showed that channel fading, the difference in delay and the tag frequency dispersion can be used for easier separation of colliding signals in a multipacket receiver in [13]. In [14], Ricciato et al achieved a 20% to 25% gain in throughput by applying inter-frame successive interference cancellation (ISIC) with respect to traditional intra-frame SIC.…”
Section: Related Workmentioning
confidence: 99%
“…Under the singlereceive-antenna detection scheme category, Zero Forcing (ZF) and Successive Interference Cancellation (SIC) are used in [6]. Maximum Likelihood (ML) sequence decoders are considered in [11][12][13].…”
Section: Related Workmentioning
confidence: 99%
“…Although a typical RFID Reader may only communicate with at most one Tag at a time based on current single-Tag detection techniques, it has been demonstrated that multi-packet reception is practically feasible with various novel ad-hoc algorithms, such as Zero Forcing (ZF) and Successive Interference Cancellation (SIC) [6], Zero Constant Modulus (ZCM) [7], Maximum Likelihood (ML) [11][12][13], etc.. Hence, it is realistic to assume that on the physical layer the Reader can separate and decode collided Tag signals.…”
Section: Epc Gen2 Overview and Proposed Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Multipacket reception, as a result of the implementation of collision recovery techniques, has been extensively investigated in the literature [6][7][8][9][10][11][12][13] yielding highly reliable results. The common aspect of these works is the exploitation of diversity-combining techniques for blind source separation, i.e.…”
Section: Introductionmentioning
confidence: 99%